2019
DOI: 10.1108/jkm-06-2018-0370
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into agile learning processes and knowledge sharing practices to prevent identity theft in the online retail organisations

Abstract: Purpose Lack of individual awareness of knowledge sharing practices to prevent identity theft is a significant issue for online retail organisations (OROs). Agile learning processes and sharing of knowledge is essential, but the lack of relevant training inhibits these processes within the online industry. This study aims to identify the inhibiting factors in agile learning and knowledge sharing process with recommendations for best practice for organisations and staff to effectively share knowledge on identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 87 publications
(148 reference statements)
0
1
0
Order By: Relevance
“…Moreover, empirical research confirms that trust is the basis for sound management of agile teams. For example, knowledge transfer management requires trust, which must be transparent and rapid to maintain agile potential [56]. Additionally, it has been demonstrated that interpersonal trust in agile managed organizations significantly affects the innovative potential of the enterprise [57].…”
Section: The Link Between Agile Leadership and Interpersonal Trustmentioning
confidence: 99%
“…Moreover, empirical research confirms that trust is the basis for sound management of agile teams. For example, knowledge transfer management requires trust, which must be transparent and rapid to maintain agile potential [56]. Additionally, it has been demonstrated that interpersonal trust in agile managed organizations significantly affects the innovative potential of the enterprise [57].…”
Section: The Link Between Agile Leadership and Interpersonal Trustmentioning
confidence: 99%